Biochemical and ultrastructural changes in rabbit sclera after treatment with 7-methylxanthine, theobromine, acetazolamide, orl-ornithine. Issue 12 (1st December 1999) - Trier, Klaus; Olsen, Elith Bjarne; Kobayashi, Takasi; Ribel-Madsen, Søren Munk
Abstract : AIMS: To examine a possible effect of 7-methylxanthine, theobromine, acetazolamide, orl -ornithine on the ultrastructure and biochemical composition of rabbit sclera. METHODS: Groups of pigmented rabbits, six in each group, were dosed during 10 weeks with one of the substances under investigation, and one untreated group was the control. Samples of anterior and posterior sclera were taken for determination of hydroxyproline, hydroxylysine, proline, proteoglycans, uronic acids and dermatan sulphate, chondroitin sulphate, and hyaluronic acid. Sections were examined with electron microscopy, and the diameter of the individual collagen fibrils was measured. RESULTS: Treatment with theobromine produced a significant increase in the contents of hydroxylysine, hydroxyproline, and proline in both anterior and posterior sclera, while 7-methylxanthine increased the contents of hydroxyproline and proline selectively in posterior sclera. Acetazolamide, on the other hand, significantly decreased the contents of hydroxyproline and proline in samples from anterior sclera. Uronic acids in both anterior and posterior sclera were significantly reduced by treatment with 7-methylxanthine, and l -ornithine significantly reduced uronic acids in posterior sclera. An inverse correlation between contents of hydroxyproline and uronic acids was found. The mean diameter of collagen fibrils was significantly higher in the posterior sclera from rabbits treated with 7-methylxanthine or theobromine, and significantly lower in rabbits treated with acetazolamide or l -ornithine compared with controls. In the anterior sclera, fibril diameter was significantly reduced in all treatment groups compared with controls. A positive, significant correlation between fibril diameter and content of hydroxyproline and proline was found in posterior sclera. CONCLUSION: 7-Methylxanthine, a metabolite of caffeine, increases collagen concentration and the diameter of collagen fibrils in the posterior sclera, and may be useful for treatment or prevention of conditions associated with low level and/or inferior quality of scleral collagen, such as axial myopia, chronic open angle glaucoma, and possibly neovascular age related macular degeneration. The apparent loss of collagen induced by chronic treatment with acetazolamide should be taken into consideration as a potentially harmful side effect. These results may indicate that scleral biochemistry and ultrastructure are influenced by the retinal pigment epithelium. One possible explanation is that the scleral fibroblasts which produce the collagen are sensitive to changes in the physiological electric field created by the retinal pigment epithelium.